2022
DOI: 10.1111/luts.12436
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamically proven lower urinary tract dysfunction in children after COVID‐19: A case series

Abstract: Case Since the declaration of COVID‐19 as a pandemic, other unexpected symptoms related to the infection besides the respiratory system have been reported. Although a few case reports have revealed that adult patients with COVID‐19 also complained of urinary frequency and nocturia, the exact pathophysiology is still unclear. In this case series, we present three children aged 14 to 17 years with urodynamically proven lower urinary tract dysfunction (LUTD) following COVID‐19. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The exaggerated release of pro-inflammatory molecules also identified as “cytokine storm” can stimulate inflammation and demyelination of the pudendal nerve triggering bladder and bowel incontinence. 14 In contrast, it has been reported that an identical structural disorder can also lead to urinary and fecal retention through not entirely understood mechanisms. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The exaggerated release of pro-inflammatory molecules also identified as “cytokine storm” can stimulate inflammation and demyelination of the pudendal nerve triggering bladder and bowel incontinence. 14 In contrast, it has been reported that an identical structural disorder can also lead to urinary and fecal retention through not entirely understood mechanisms. 15 …”
Section: Discussionmentioning
confidence: 99%
“…This paper involves three children aged 14-17 years who presented with urinary retention and required clean intermittent catheterization after a median interval of three months. The authors performed urodynamics and showed a-contractile detrusor in two patients and hypo-contractile detrusor in one patient)[ 5 ]. Our study did not involve invasive urodynamics but had some discordant findings.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review suggested dysregulation of renin-angiotensin system, the inflammatory process in the prostate, the role of androgen receptors in prostate, or other metabolic disorders as possible mechanisms for exacerbation in BPH with COVID-19[ 4 ]. Currently, there is only one case series about this topic in children[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they did not state how long after acute COVID the patients were evaluated. In another study consisting of a small case series, persistent LUTS and urodynamic abnormalities have been shown months after acute SARS-CoV-2 infection in teenagers (15). Authors proposed that clinicians should be aware of a recent COVID-19 infection in patients with sudden onset lower urinary tract dysfunction.…”
Section: Introductionmentioning
confidence: 99%